2020
DOI: 10.3390/md19010005
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Glycosides with a Triazole Moiety for Marine Antifouling Applications: Synthesis and Biological Activity Evaluation

Abstract: Over the last decades, antifouling coatings containing biocidal compounds as active ingredients were used to prevent biofouling, and eco-friendly alternatives are needed. Previous research from our group showed that polymethoxylated chalcones and glycosylated flavones obtained by synthesis displayed antifouling activity with low toxicity. In this work, ten new polymethoxylated flavones and chalcones were synthesized for the first time, including eight with a triazole moiety. Eight known flavones and chalcones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 60 publications
(36 reference statements)
1
21
0
Order By: Relevance
“…Compounds 2a and 2b were synthesized and characterized following previously reported methods and 1 H and 13 C NMR data were in accordance with the previously reported [24] and [16,23], respectively.…”
Section: Synthesis Of Propargyloxy Acetophenone 2a and 2bmentioning
confidence: 73%
See 2 more Smart Citations
“…Compounds 2a and 2b were synthesized and characterized following previously reported methods and 1 H and 13 C NMR data were in accordance with the previously reported [24] and [16,23], respectively.…”
Section: Synthesis Of Propargyloxy Acetophenone 2a and 2bmentioning
confidence: 73%
“…For instance, bromotyramine hybrids containing a 1,2,3-triazole ring were described as inhibitors of biofilm formed by marine bacteria [15]. Recently, previous research developed by our group has identified a chalcone glycoside with a 1,2,3-triazole moiety with promising AF activity against macro and microfouling species, without ecotoxicity to a non-target marine organism [16].…”
Section: Synthesis and Structure Elucidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the biocides currently used in antifouling coatings have proved to be harmful, the search for effective and low toxic antifouling agents is an urgent request [ 38 , 126 ]. In an attempt to develop more environmentally friendly antifouling compounds, Pereira et al (2021) synthesized a series of glycosylated chalcones and flavones conjugated through a triazole ring, through CuAAC reaction [ 127 ]. Compounds were screened for in vivo anti-settlement activity against the macrofouling organism Mytilus galloprovincialis .…”
Section: Other Activitiesmentioning
confidence: 99%
“…Tertiary colonization occurs with the capture of particles and organisms, such as the larvae of marine macro-organisms, including macroalgae, sponges, cnidarians, polychaetes, mollusks, barnacles, bryozoans, and tunicates [ 5 ]. In the last five years, several antifouling (AF) compounds capable of inhibiting the settlement of the macrofouler, Mytilus galloprovincialis (mussel) larvae, were synthesized by some of us [ 6 , 7 , 8 , 9 , 10 , 11 ]. After structure-AF activity relationship studies on several gallic acid derivatives, we recently discovered that N -(2-aminoethyl)-3,4,5-trihydroxybenzamide hydrobromide (GBA26) ( Figure 1 ) exhibited an optimized potency against the larvae settlement of this mussel with higher LC 50 /EC 50 than the previous parent compound and the emerging biocide Econea ® (tralopyril) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%